We need to determine the solutions of u(v(t)) = 0 given that u(t) = t^2 - 16 and v(t) = t + 2.

u(v(t)) = 0

=> u( t + 2) = 0

=> (t + 2)^2 - 16 = 0

=> (t + 2)^2 - 4^2 = 0

=>...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We need to determine the solutions of u(v(t)) = 0 given that u(t) = t^2 - 16 and v(t) = t + 2.

u(v(t)) = 0

=> u( t + 2) = 0

=> (t + 2)^2 - 16 = 0

=> (t + 2)^2 - 4^2 = 0

=> (t + 2 - 4)(t + 2 + 4) = 0

=> (t - 2)( t + 6) = 0

t - 2 = 0 => t = 2

t + 6 = 0 => t = -6

**We get the solutions of u(v(t)) = 0 as t = 2 and t = -6**